2018
DOI: 10.1002/adma.201800863
|View full text |Cite
|
Sign up to set email alerts
|

The Regulating Role of Carbon Nanotubes and Graphene in Lithium‐Ion and Lithium–Sulfur Batteries

Abstract: The ever-increasing demands for batteries with high energy densities to power the portable electronics with increased power consumption and to advance vehicle electrification and grid energy storage have propelled lithium battery technology to a position of tremendous importance. Carbon nanotubes (CNTs) and graphene, known with many appealing properties, are investigated intensely for improving the performance of lithium-ion (Li-ion) and lithium-sulfur (Li-S) batteries. However, a general and objective underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
255
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(256 citation statements)
references
References 164 publications
1
255
0
Order By: Relevance
“…It is well known that the insulating nature of sulfur and lithium sulfides, shuttling effect of high‐order polysulfide Li 2 S x (4 ≤ x ≤ 8), and volumetric expansion/shrinkage during discharging/charging are the main challenges impeding the commercial process of LSBs . Here, the corporation of the virus‐derived materials and sulfur is potential to well resolve these problems and provides a new avenue for construction of high‐performance lithium–sulfur batteries.…”
Section: Virusmentioning
confidence: 99%
“…It is well known that the insulating nature of sulfur and lithium sulfides, shuttling effect of high‐order polysulfide Li 2 S x (4 ≤ x ≤ 8), and volumetric expansion/shrinkage during discharging/charging are the main challenges impeding the commercial process of LSBs . Here, the corporation of the virus‐derived materials and sulfur is potential to well resolve these problems and provides a new avenue for construction of high‐performance lithium–sulfur batteries.…”
Section: Virusmentioning
confidence: 99%
“…The unstacked graphene layers are able to offer an ultralow local current density, which is five orders of magnitude lower than that of the bulk counterpart . The interaction of 2D structures and Li + /Na + or electrons tends to shorten the length of diffusion, significantly improving electrochemical performance of LIBs . This results in a stabilized capacity of higher than 1300 mAh g −1 and a notable power density of 6500 W kg −1 with excellent cycling stability .…”
Section: Lithium Storage Applicationsmentioning
confidence: 99%
“…Moreover, the performance of an electrode material not only depends on the building units but also largely on how they are assembled . As a result, the integration of electrode materials with one, two, and three dimensionalities have become a research hotspot for a long time . These desired structures show great potential to overcome the shortcomings under various conditions, offering an intelligent way to expand the boundaries of LBs.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume [79] expansion. [80][81][82]90,[91][92][93][94][95][96] The strategy for the feasible nanostructured assembly of a three-dimensional porous graphene/ niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high-rate capability at practical levels of mass loading. Subsequently, Zhao et al 84 found that densely packed Li x M/graphene foils (M = Si, Sn, or Al) would serve as air-stable and freestanding anodes guaranteeing stable structures and exceptional cyclabilities ( Figure 10).…”
Section: Batteriesmentioning
confidence: 99%